Pattern of antibody responses to Plasmodium falciparum antigens in individuals differentially exposed to Anopheles bites - Aka, Kakou G. (Malar J, 2020)
BACKGROUND: In malaria-endemic areas, human populations are frequently exposed to immunomodulatory salivary components injected during mosquito blood feeding. The consequences on pathogen-specific immune responses are not well known. This study evaluated and compared the humoral responses specific to merozoite stage vaccine candidates of Plasmodium falciparum, in children differentially exposed to Anopheles bites in a natural setting. METHODS: The cross-sectional study was carried out in Bouaké (Côte d’Ivoire) where entomological data and blood samples from children (0–14 years) were collected in two sites with similar malaria prevalence. Antibody (IgG, IgG1, IgG3) responses to PfAMA1 and PfMSP1 were evaluated by ELISA. Univariate and multivariate analysis were performed to assess the relationship between the immune responses to P. falciparum antigens and exposure to Anopheles bites in the total cohort and in each site, separately. The individual level of exposure to Anopheles bites was evaluated by quantifying specific IgG response to the Anopheles gSG6-P1 salivary peptide, which represents a proxy of Anopheles exposure. RESULTS: The anti-Plasmodium humoral responses were different according to the level of exposure of children, with those highly exposed to Anopheles presenting significantly lower antibody responses to PfMSP1 in total population (IgG and IgG3) and in Petessou village (IgG, IgG1, IgG3). No significant difference was seen for PfAMA1 antigen between children differently exposed to Anopheles. In Dar-es-Salam, a neighbourhood where a high Culex density was reported, children presented very low antibody levels specific to both antigens, and no difference according to the exposure to Anopheles bites was found. CONCLUSION: These findings may suggest that immunomodulatory components of Anopheles saliva, in addition to other factors, may participate to the modulation of the humoral response specific to Plasmodium merozoite stage antigens. This epidemiological observation may form a starting point for additional work to decipher the role of mosquito saliva on the modulation of the anti-Plasmodium acquired immunity and clinical protection in combining both field and ex vivo immunological studies.